Promoting oil seed crops in Pakistan: Prospects and constraints - Rana, Abdul Wajid; Gill, Sitara; Akram, Iqra (International Food Policy Research Institute, 2022)
Oilseeds in Pakistan characterizes a policy failure as the production of oilseeds as well as edible oil has been on the decline despite various initiatives. The country has been augmenting growing demand-supply gap through imports since early 1970. The domestic production contributes only 13-15 percent of the total consumption while 85-87 percent is met through imports. Per capita consumption of vegetable oil has risen from 5.31 kg in 1973-74 to 20 kg in 2018 and is likely to move to 22 kg by 2028 projecting total consumption to 6.5 million tons by 2028 against current local production of less than 0.5 million tons, widening the demand-supply gap further. The import bill for these products has reached over US$4 billion in FY2021 which is straining the balance of trade and the balance of payment. With global uncertainties and challenges facing the oilseeds sector including the sharp price fluctuations and market instability and favorable tariffs for imports, the import bill is likely to move upward underscoring the need for well thought out policy and planning.